(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1990)
Sediments mainly carbonatic, with fossil remains, interbedded in calcalkaline formations related to early Oligo-Miocene volcanic cycles, have been detected in three areas of southern Sardinia. It is thought that these sediments may have been deposited in small lake basins, during periods of volcanic inactivity.